We do not select, nor are we choosy: reproductive biology of Strepsiptera (Insecta). (18th June 2015) - Kathirithamby, Jeyaraney; Hrabar, Michael; Delgado, Juan A.; Collantes, Francisco; Dötterl, Stefan; Windsor, Donald; Gries, Gerhard
<x xml:space="preserve">Abstract</x> The cryptic entomophagous parasitoids in the order Strepsiptera exhibit specific adaptations to each of the 34 families that they parasitize, offering rich opportunities for the study of male–female conflict. We address the compelling question as to how the diversity of Strepsiptera (where cryptic speciation is common) arose. Studying 13 strepsipteran families, including fossil taxa, we explore the genitalic structures of males, the free‐living females of the Mengenillidia (suborder), and the endoparasitic females of the Stylopidia (suborder). Inferring from similarity between aedeagi of males either between congeners, heterogeners, or between species within the same taxonomic family, the same of which is true of the cephalothoraces of females, we predict that male–female conflict and a co‐evolutionary morphological arms race between sexes is not likely to exist in most species of Strepsiptera. We then review the non‐genitalic structures that play a role during sexual communication, and present details of copulatory behaviour. We conclude that Strepsiptera fall within the synchronous sensory exploitation model where short‐lived males take advantage of a pre‐existing sensory system involving pheromone signals emitted by females.